Multifarious microbial biostimulants promote growth in Arachis hypogaea L. - Eswaran, Sakthi Uma Devi; Sundaram, Lalitha; Siang, Tan Ching; Alharbi, Sulaiman Ali; Alahmadi, Tahani Awad; Kadam, Suhas Kishor (Frontiers in Sustainable Food Systems, 2023)
Plant Growth Promoting Rhizobacteria (PGPR), a microbial biostimulant, has been widely studied to stimulate plant growth through the induction of natural biological processes. However, the lack of successful validation in the open fields remains a barrier to marking their standard in agriculture. Therefore, the present research aimed to highlight the potential of PGPR biostimulants via in vitro studies and demonstrate the planta evaluation in an oilseed crop, Arachis hypogaea L. (Groundnut), under pot and field trials. The two rhizobacterial strain was identified as Pseudomonas fluorescens and Bacillus subtilis by 16s rRNA gene sequence analysis. Both strains were functionally screened for plant growth-promoting traits. Pot and field trials were conducted where seeds were inoculated with PGPR biostimulants and harvested at 30 and 90 days. Biostimulant treatments were applied as single and co-inoculation in groundnut, and the growth factors, biochemical parameters, yield, and seed quality were analyzed. The study inferred that the consortium of PGPR biostimulants significantly (p<0.05) showed the highest growth, photosynthetic pigments, nodulation status, leghaemoglobin content, yield attributes, and biofortification of seed nutrients in oilseed crops under both pot and field conditions than un-inoculated control. This study supports applying PGPR as microbial biostimulants through successful open field trials to facilitate its implementation as a viable and potential agricultural product to synthetic fertilizers, thereby influencing sustainable and stable crop production.